TRANSLATION OF PRODUCT LABELS AND PACKAGING (Ustozlar uchun, 2025)
This paper explores the importance, challenges, and techniques of translating product labels and packaging in a globalized market. Accurate translation of labels ensures consumer safety, compliance with international regulations, and effective marketing communication. The study examines linguistic, cultural, and technical factors that influence translation quality, including terminology consistency, measurement conversions, and culturally appropriate messaging. Special attention is given to the role of localization in adapting product information to target markets. The research concludes that professional translation and cultural adaptation are essential for building consumer trust and enhancing a product’s competitiveness in foreign markets.